May FB ka na ba? navigating students’ visit in social media networks - Babaran, Nilda O. (Linguistics and Culture Review, 2021)
Without a doubt, social media is the most influential networking tool on the world. This research demonstrates the influence of social media on people’s life. It investigates how social media platforms such as YouTube, Twitter, Instagram, Messenger, Facebook, Linkiden, Multiply, and others manage and navigate the everyday lives of students who utilize these platforms for academic purposes. In the research, descriptive techniques are employed, and the sampling strategy is based on Slovin’s Formula. Students were found to regularly use YouTube, Facebook, and other social networking sites. As a consequence, the networks were easy to use, as were the phones they utilized. They often utilize these services to fulfill the requirements of their friends as well as their scholastic responsibilities, enabling them to establish additional friends outside of their nation. Social networking sites, when utilized properly and in moderation, may be extremely helpful to children’s scholastic growth and development. Excessive usage may result in addiction and be detrimental to one’s health. It was highly recommended that, students could utilize extra educational networking sites such as research gate and google scholar, scribd, and sage to become more educationally oriented and meet academics and professionals in the aforementioned networks.